The Influence of Social Capital on Corn Productivity: Empirical Evidence of Female Farmers in Sumenep Regency, Indonesia - Deswitanti, Anggie Putri; Priyanto, Moh. Wahyudi; Nugroho, Taufik Rizal Dwi Adi (HABITAT, 2024)
Corn production in Bragung Village, Guluk-Guluk Subdistrict, tends to be fluctuating, but the consumption of corn continues to increase. The fluctuation in corn production is not necessarily due to climate change, which is a hindering factor to achieve 80% of the national corn production contribution. Therefore, efforts are needed to increase corn production by considering social capital through bonding, bridging, and linking roles. The purpose of this research is to determine the influence of social capital on corn productivity in Bragung Village, Guluk-Guluk Subdistrict, Sumenep Regency, Madura. Data collection was carried out through observation and interviews by filling out questionnaires. The research method used is ordinary least squares analysis (OLS) on 71 female farmers selected through simple random sampling. The analysis results show that factors that have a significant and positive influence on corn productivity are bonding, education, and experience. Factors that do not have a significant impact are bridging, linking, age, and sales quantity. Based on the research results, efforts that can be made to increase corn productivity include strengthening relationships, especially in corn farming, such as discussing and helping each other.